Perceptions of Illness Control, Coherence, and Self-Efficacy Following a Web-Based Lifestyle Program for Multiple Sclerosis: A Qualitative Analysis of Semistructured Interviews - Rebekah Davenport; William Bevens; Sandra Neate; Pia Jelinek; Maggie Yu; George Jelinek; Jeanette Reece (JMIR Publications, 2024)
BackgroundEvidence suggests that illness perceptions held by people living with multiple sclerosis (MS) impact affective distress and physical health outcomes. In a randomized controlled trial, we developed 2 MS Online Courses-the standard care course and the intervention course (IC). The IC was adapted from an evidence-based lifestyle program. Modifying lifestyle risk factors offers an opportunity to impact illness perceptions. Research on illness perceptions in people living with MS has focused predominately on quantitative methods. ObjectiveThis study aimed to explore the experiences and health outcomes of randomized controlled trial participants, including individuals' perceived changes in attitudes toward MS and their health (ie, illness perceptions). MethodsQualitative responses provided by 38 participants (22 in the IC and 16 in the standard care course) were derived from semistructured interviews 1 month after completing the MS Online Course. The impact of course engagement and lifestyle modification on illness perceptions was explored using inductive thematic analysis. ResultsThemes of changes in illness perceptions were most prominent in the IC arm. Qualitative responses from 22 people living with MS informed the development of three themes: "self-efficacy for disease management," "personal control," and "illness coherence." ConclusionsFindings provide novel insights into the formation and modification of illness perceptions. Lifestyle modification may serve as a valuable adjunct to clinician-administered therapies, improving the sense of personal control over MS, illness coherence, and self-efficacy for disease management. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12621001605886; https://tinyurl.com/2vyve9p9 International Registered Report Identifier (IRRID)RR2-10.1186/s12883-023-03298-0